Intergenerational Equity and Exhaustible Resources - Solow, R. M. (Review of Economic Studies, 1974)
Intergenerational Equity and Exhaustible Resources Get access R. M. Solow R. M. Solow Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 5, December 1974, Pages 29–45, https://doi.org/10.2307/2296370 Published: 01 December 1974